Genome-wide analysis of OFP gene family in pepper (Capsicum annuum L.) - Luo, Yin; Yang, Shimei; Luo, Xirong; Li, Jing; Li, Tangyan; Tang, Xiangqun; Liu, Feng; Zou, Xuexiao; Qin, Cheng (Frontiers in Genetics, 2022)
Ovate family proteins (OFPs) are transcriptional inhibitors that regulate plant growth and development and play important roles in the synthesis of secondary cell walls during pollen development. This study identified the pepper OFP gene family based on the genome-wide analysis and used bioinformatics methods to provide a fundamental profile of the gene family. 74 OFP genes with typical Ovate domain were identified in cultivated pepper Zunla-1, wild pepper Chiltepin and CM334. Chromosome mapping revealed that CazOFP genes were unevenly distributed on 11 chromosomes and Chr00 in Zunla-1, CacOFP genes on 12 chromosomes in Chiltepin, and CamOFP genes on 12 chromosomes and two Scaffflods in CM334. Gene structure analysis revealed that CaOFP genes possessed 1-3 exons, and the analysis of physicochemical properties suggested that CaOFPs were hydrophilic. Many cis-acting elements were identified in the promoter region of CaOFP genes, including ABRE, ARE, Box 4, G-box, TC-rich, and TCT-motif. The expression patterns of pepper at different growth stages showed that CaOFP genes were actively involved in the growth and fruit development of pepper, and CazOFP16 and CazOFP17 were actively involved in response to multiple hormones and stress events. qRT-PCR was also used to verify the expression of CazOFP gene in two developmental stages of seven pepper varieties with different fruit shapes, and it was found that CaOFP genes may be involved in the formation of fruit type in pepper. This study provides theoretical and practical evidence for future research on the OFP gene family.